Improving Students’ Reading Comprehension Ability Using Task Based Language Teaching at MTs Negeri 1 Yogyakarta - Ruslina Tri Astuti (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This study was conducted in response to the fact that the students’ reading comprehension ability was much lower than they should have achieved. It was caused by several reasons. One of them was related to the poor teaching learning process. In this study, Task-based Language Teaching (TBLT) was used to improve the teaching learning process and the students’ reading comprehension ability. This research was a Classroom Action Research (CAR) study and it was done in two cycles. Observation and interviews were used to collect data which were then analyzed qualitatively. Students’ achievement of daily-test, the students’ selfreflection in the form of rating format and the students’ achievement of post-tests were used in order to support the data collected. The results of this study indicate that TBLT can improve not only the teaching learning process but also the class 8D of MTs Negeri 1 Yogyakarta students’ reading comprehension ability in recount text. It is shown that the students are interested to learn reading and they enjoy the reading teaching learning process using TBLT. The students’ average score before the action is 62.81. In the first cycle the mean score is 72.03, meanwhile the mean score in the second cycle is 79.06. It means that there is an improvement of students’ scores from cycle to cycle. Keywords: Reading Comprehension Ability, Task-Based Language Teaching AbstrakPenelitian ini dilakukan untuk menanggapi fakta bahwa kemampuan memahami bacaan siswa lebih rendah dari yang seharusnya mereka capai. Hal ini disebabkan oleh beberapa sebab, salah satunya terkait dengan proses belajar mengajar yang buruk. Dalam penelitian ini, Taks-Based Language Teaching (TBLT) digunakan untuk meningkatkan proses belajar mengajar dan kemampuan memahami bacaan siswa. Penelitian ini adalah Penelitian Tindakan Kelas (PTK) dan dilakukan dalam duasiklus. Observasi dan wawancara digunakan untuk mengumpulkan informasi yang kemudian diolah secara kualitatif. Hasil tes harian siswa, rating format siswa, dan hasil postes digunakan untuk mendukung data kualitatif yang diperoleh. Hasil penelitian mengindikasikan bahwa TBLT tidak hanya dapat meningkatkan proses belajar mengajar namun juga kemampuan siswa kelas 8D di MTs Negeri 1 Yogyakarta dalam memahami bacaan recount. Terlihat bahwa siswa tertarik untuk belajar membaca dan mereka menikmati proses belajar mengajar membaca menggunakan TBLT. Nilai rata-rata siswa sebelum penelitian adalah 62.81, sedangkan nilai rata-rata postes siswa pada siklus pertama meningkat menjadi 72.03, dan pada postes siklus kedua menjadi 79.06. Ini berarti ada peningkatan nilai rata-rata siswa dari siklus ke siklus. Kata Kunci: Kemampuan Memahami Bacaan, Task-Based Language Teaching